Political culture and democracy in developing countries - Diamond, Larry Jay. (Boulder : Lynne Rienner, 1994)
This textbook edition of this work has been abridged to convey its core arguments in a format appropriate for classroom use. It explores the complex and reciprocal interactions between a society's dominant beliefs, values, and attitudes about politics and the nature of its political system.
Foreword : the return to political culture / Gabriel A. Almond -- Introduction : political culture and democracy / Larry Diamond -- Culture and democratization in India / Richard Sisson -- Between liberalism and statism : African political cultures and democracy / Naomi Chazan -- Paths to democracy and the political culture of Costa Rica, Mexico, and Nicaragua / John A. Booth & Mitchell A. Seligson -- A nonparadigmatic search for democracy in a post-Confucian culture : the case of Taiwan, R.O.C. / Ambrose Y.C. King -- Automomous groups as agents of democratic change in communist and post-communist eastern Europe / Christine M. Sadowski -- State elites and democratic political culture in Turkey / Ergun Ozbudun -- Christian democracy, liberation theology, and political culture in Latin America / Paul E. Sigmund -- Causes and effects / Larry Diamond.
Cover title: Political culture & democracy in developing countries.
Includes bibliographical references and index.
Keywords: Political culture -- Developing countries; 89.53 political culture; Political culture; Democratie; Cultura; Democracia; Developing countries -- Politics and government; Developing countries -- Politics; Aufsatzsammlung